Effect of various temperature and storage duration on setting time of OREGA sealer - Bambang Sunarko (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2008)
Background: Choosing the right rigid material and root canal paste are crucial in the success of root canal obturation. N2 is a root canal paste containing formaldehyde, which is toxic and carcinogenic. Whilst zinc oxide, resorcin, eugenol, glycerin, and hydrochloric acid, abbreviated as OREGA, are considered a safer root canal paste. In order to perform good obturation, root canal paste’s setting time plays an important role. This is connected with how long and in what temperature the paste’s substances are stored. Purpose: This experiment was performed to find out the effect of various temperature and storage duration on the setting time of OREGA sealer. Method: OREGA and N 2sealers were used as samples. Eighty sealer samples were produced for both sealers providing 10 samples foe each testing category. Each of these samples were stored in 27°C room temperature, 4°C refrigerator temperature, and put into storage for the duration of 0, 1, 2, and 3 months. After these treatments, the samples were tested and analyzed. Result: Data collected were analyzed by two-way ANOVA, showing no significant difference of the setting time among temperature and storage duration (p> 0.05). Conclusion: Temperature and storage duration do not affect the setting time of OREGA root canal paste.